Reintroducing Acheloios Hermotos of Parion - Molinari, Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2022)
Usually when I receive an email about a ‘new’ Acheloios it turns out to be a false positive—somehow over the years an encrustation, overstrike, or other phenomenon has reconfigured the coin so that the creature looks just like a man-faced bull. This happened many times when Dr. Sisci and I were writing ΠΟΤΑΜΙΚΟΝ, in which case we had examples from such places as Pantikapaion, Euboia, and even Knossos, a coin that almost forced a rewrite of the entire narrative. But for every dozen or so false-positives we find the real deal: the silver-eddying Acheloios, and there is nothing quite like being the first to see him after so many years in hiding. This essay documents one such occurrence, a seemingly bona fide Acheloios discovered by a man named John Miracle, and reintroduces a deity that has not been worshipped in cult for over two millennia: Acheloios Hermotos, of Parion.